Absence of classical and atypical (H- and L-) BSE infectivity in the blood of bovines in the clinical end stage of disease as confirmed by intraspecies blood transfusion. (26th January 2021) - Balkema-Buschmann, Anne; Ziegler, Ute; Priemer, Grit; Tauscher, Kerstin; Köster, Frauke; Ackermann, Ivett; Fatola, Olanrewaju I.; Balkema, Daniel; Schinköthe, Jan; Hammerschmidt, Bärbel; Fast, Christine; Ulrich, Reiner; et al.
Abstract : While the presence of bovine spongiform encephalopathy (BSE) infectivity in the blood of clinically affected sheep has been proven by intraspecies blood-transfusion experiments, this question has remained open in the case of BSE-affected cattle. Although the absence of infectivity can be anticipated from the restriction of the agent to neuronal tissues in this species, evidence for this was still lacking. This particularly concerns the production and use of medicinal products and other applications containing bovine blood or preparations thereof. We therefore performed a blood-transfusion experiment from cattle in the clinical end stage of disease after experimental challenge with either classical (C-BSE) or atypical (H- and l -) BSE into calves at 4–6 months of age. The animals were kept in a free-ranging group for 10 years. Starting from 24 months post-transfusion, a thorough clinical examination was performed every 6 weeks in order to detect early symptoms of a BSE infection. Throughout the experiment, the clinical picture of all animals gave no indication of a BSE infection. Upon necropsy, the brainstem samples were analysed by BSE rapid test as well as by the highly sensitive Protein Misfolding Cyclic Amplification (PMCA), all with negative results. These results add resilient data to confirm the absence of BSE infectivity in the donor blood collected from C-, H- and l -BSE-affected cattle even in the final clinical phase of the disease. This finding has important implications for the risk assessment of bovine blood and blood products in the production of medicinal products and other preparations.